"I can teach what's in the book": Understanding the why and how behind teachers' implementation of a social‐emotional learning (SEL) focused curriculum in rural Malawi. (30th December 2021) - Lee, Jeongmin; Simmons Zuilkowski, Stephanie
Abstract : Contextualizing the role of teachers in social‐emotional learning (SEL) in Malawi, we examine how teachers' comfort with, commitment to, and perceived school culture toward SEL relate to their actual teaching of it. Using surveys from 432 primary school teachers (20–60 years old), we found teacher comfort and supportive school culture were positively related to integration of SEL into classroom instruction, while commitment had no statistically significant relationship with implementation. We explore plausible explanations for these findings by interviewing 42 teachers. Together, our findings highlight the importance of teacher support systems and cultural compatibility of the curriculum for successful SEL implementation.